An in situ study using caged Nucella lapillus and Crassostrea gigas to monitor TBT induced bio-effects in Irish coastal waters - Giltrap, M.; Macken, A.; Minchin, D.; Davoren, M.; McGovern, E.; Foley, B.; Strand, J.; McHugh, B. (2007)
Tributyltin (TBT) is recognised as an effective antifouling agent for use in marine paints for shipping and on aquaculture fish cages and in other marine applications. It has however been found to be toxic to many species of gastropods and can affect these species at concentrations as low as 2ng/L. TBT has been linked to shell thickening and reduced meat yields in oysters and perhaps more significantly to the onset of imposex, i.e. the imposition of male sexual organs on female gastropods, with this index being internationally recognised as a bio-indicator of TBT pollution. Species of the gastropod, Nucella lapillus showing no imposex and juvenile pacific oysters Crassostrea gigas were transplanted in cages at test sites around the Irish coast. Mussels (Mytilus edulis) were provided as a food source for the gastropods. The degree of imposex in the gastropod as measured by the vas deferens sequence index (VSDI) and the extent of shell thickening in the oysters was investigated at t=0 and t=18 weeks. The concentrations of TBT in tissue representative samples of each of the test species were also measured at t=0 and t=18 weeks. Sediment samples were also taken from each site and analysed for organotin speciation in the <2mm and <63ìm fraction at t=0 and t=18 weeks. It is anticipated that in the absence of resident gastropod populations the application of such cost effective caging techniques may assist in provision of environmental quality information at potential hotspot locations. Results of analysis will be presented.